Should We Routinely Test for Chordee in Patients with Distal Hypospadias? - (:unkn) unknown (GEORG THIEME VERLAG KG, 2015)
ObjectivesThe aim of this study was to determine the incidence of chordee in distal hypospadias and compare our intraoperative findings with those reported by the families of patients and to determine if routine testing for chordee should be performed in patients with distal hypospadias. Material and MethodsSurgical reports and medical files of distal hypospadias patients operated from January 2008 to January 2013 were prospectively reviewed. The type of hypospadias, family's report of chordee, intraoperative finding of chordee and its degree were noted. All patients were tested for chordee intraoperatively after degloving. ResultsA total of 156 patients of which 27 had glandular, 61 coronal, and 68 subcoronal hypospadias were included in the study. Chordee was found in 52 patients (33.3%) intraoperatively, whereas only 15 families (9.6%) reported chordee preoperatively. ConclusionThere is risk of chordee in patients with distal hypospadias that needs to be accurately identified and corrected. Families are not always aware of the presence of chordee.
Keywords: chordee; distal hypospadias; TIPU; PENILE CURVATURE; DORSAL PLICATION; TRENDS